Smart multifunctional nanoparticles design as sensors and drug delivery systems based on supramolecular chemistry - Gontero, Daniela (2017)
Supramolecular chemistry is a well-known field that, applied to analytical chemistry gives, as a result, supramolecular analytical chemistry. Based in its interactions, this field is part of a new area of nanomedicine, called supramolecular medicine. In order to improve the detection of biological molecules to be applied in cell tracking, health problems and biological events, supramolecular chemistry has lately been combined with supra-nanostructures design. In other words, supramolecular systems can be used as tools in the nano-design of nano-systems for the bio-recognition of biological events, host of ions and organic molecules with different structures and intrinsic chemical properties, as enhancer of the solubility, modification of surface properties, bioconjugation for the nanoparticles design, etc. The versatility of these types of systems is very wide; specifically their use in the nanosensor design using nanoparticles was not highly applied. However, in the last years, the bioconjugation of supramolecular systems, such as macrocycles and antibodies, and proteins with metallic and polymeric nanoparticles has increased, as well as the development of supramolecular nanoparticles based on host guest interactions of macrocycles. Therefore, this review focuses on the application of supramolecular systems as signal transducers in the nanosensors design for bio-recognition events, detection of biological targets, and drug delivery system. These nanosystems, as transducer hosts and building blocks, are linked to metallic and polymeric nanoparticles; and organize molecular systems for different applications.